Ameriška judikatura (akreditivi in bančne garancije) - Jus, Miran (Pravnik, 2013)
American law recognises independence principle of L/C and bank guarantees. However, this principle is not absolute, and may be limited - inter alia - with injunction procedures to prevent the issuing bank from honouring such undertaking by narrowly applied exception of clearly established (material) fraud in the transaction (fraus omnia corrumpit). In our case dispute from underlying construction contract over applicant's performance lead to arbitral award in the applicant's favour. Therefore, the court - according to the author who does not agree with the critics - correctly applied fraud rule (Rev. UCC 5-109 (1995)) and held that in light of this award, neither the beneficiary nor the local bank has a "colorable right" to demand the honour of the guarantees on first demand and counter-guarantee, respectively. Final arbitral award precluded beneficiary from demanding payments under its guarantees (res judicata), and is definitely clear and blatant evidence of unfair calling that entitles the applicant to "bear fruit" from judicial circumvention of the independence principle; i.e., established fraud by final arbitral award is sufficient condition for injunction, and court does not need to observe other case law-developed standards for issuing injunctions (e.g., whether absent the injunction applicant would suffer irreparable harm, would have adequate remedy under law, etc.).
Keywords: akreditivi; bančne garancije; bančništvo; banke; finančno pravo; United States of America; ZDA; Združene države Amerike